Pancreatitis associated with SPINK1 mutation and pancreaticobiliary maljunction - Sirichamratsakul Kulpreeya; Laochareonsuk Wison; Chiengkriwate Piyawan; Sangkhathat Surasak (Elsevier, 2020)
Chronic pancreatitis (CP) in childhood is a rare condition and its etiology varies with mainly associated with genetic abnormalities, autoimmune pancreatitis, and obstruction. The authors describe a 6-year-old girl presented with abdominal pain and diagnosed as CP with an infected peripancreatic fluid collections (peri-PFC), and found a pancreaticobiliary maljunction (PBM) together with a SPINK 1 mutation at N34S codon. This combination of an anatomical obstruction and genetic mutation should be aware, in early childhood presented with pancreatitis. Keywords: Chronic pancreatitis, Pancreaticobiliary maljunction, SPINK1 gene